Le droit de refuser un traitement psychiatrique au Québec - Gervais, Daniel (Les Cahiers de droit, 1985)
There are various types of incapacity in the civil law of Québec. The provisions of the Civil Code concerning the interdiction of incapable persons are now supplemented by various statutes. In all cases, a curator — and generally the public curator — is appointed to accept or refuse treatment for an incapable person. Except in cases of serious emergency, it is clearly established that any treatment, whether medical or psychiatric, must be preceeded by the patient's informed consent. While some recourses already exist to protect the rights of an incapable patient for whom a curator has been appointed, this is not the case for psychiatric patients who are of legal age and legally competent, but who refuse treatment. In these cases, it is suggested that the decisions of Québec courts that have recognized a « defacto incapacity » and, consequently, forcible treatment on the basis of the « parens patriae » doctrine, may be ill-founded. This opinion is based on the application of the principles of self-determination and the inviolability of the human person, and by establishing a parallel with constitutional rights recognized by American courts which are now echoed in the new Canadian Charter of Rights. The author suggests that all recourses involving refusal of treatment be referred to a centralized administrative tribunal, in the light of the reform of the Civil Code.